Complexities of emotional responses to social and non-social affective stimuli in schizophrenia - Peterman, Joel S.; Bekele, Esubalew; Bian, Dayi; Sarkar, Nilanjan; Park, Sohee (Frontiers in Psychology, 2015)
BACKGROUND: Adaptive emotional responses are important in interpersonal relationships. We investigated self-reported emotional experience, physiological reactivity, and micro-facial expressivity in relation to the social nature of stimuli in individuals with schizophrenia. METHOD: Galvanic skin response (GSR) and facial electromyography (fEMG) were recorded in medicated outpatients with schizophrenia (SZ) and demograph-ically-matched healthy controls (CO) while they viewed social and non-social im-ages from the International Affective Pictures System (IAPS). Participants rated the valence and arousal, and selected a label for experienced emotions. Symp-tom severity in the SZ, and schizotypy in CO were assessed. RESULTS: The two groups did not differ in their labeling of the emotions evoked by the stimuli, but individuals with schizophrenia were more positive in their va-lence ratings. Although self-reported arousal was similar in both groups, GSR was greater in schizophrenia, suggesting differential awareness or calibration of internal states. Both groups reported social images to be more arousing than non-social images but their physiological responses to nonsocial vs. social imag-es were different. Self-reported arousal to neutral social images was correlated with positive symptoms in schizophrenia. Negative symptoms in SZ and disor-ganized schizotypy in CO were associated with reduced fEMG. Greater corruga-tor fEMG activity for positive images in SZ indicates valence-incongruent facial expressions. CONCLUSIONS: The patterns of emotional responses differed between the two groups. While both groups were in broad agreement in self-reported arousal and emotion labels, their GSR and fEMG correlates of emotion diverged in relation to the social nature of the stimuli and clinical measures. Importantly, these results suggest disrupted self awareness of internal states in schizophrenia and under-score the complexities of emotion processing in health and disease.